Eksistensi dan Interpretasi Wanita Karier dalam Perspektif Al-Quran - Riza Arizona; Nasruddin Nasruddin (STIKes Ibnu Sina Ajibarang, 2025)
This study discusses the existence and interpretation of women's careers from the perspective of the Qur'an, with the aim of exploring the understanding of the role of women in the world of work according to Islamic teachings. Career women in the modern context often face challenges in combining their roles as mothers, wives, and professionals. However, in the Qur'an, there are principles that provide space for women to contribute in various areas of life, including work, as long as they do not conflict with Islamic moral and ethical values. This study uses an interpretation approach to analyze relevant verses, as well as examines the social and historical contexts that influence the understanding of career women. The results of the study indicate that the Qur'an provides freedom for women to pursue a career, on condition that they pay attention to the balance between domestic duties and social rights and maintain self-integrity in the work environment. Therefore, the interpretation of the role of career women in the Qur'an can be more relevant and contextual if viewed from a more flexible perspective, while still adhering to the values ​​of justice and welfare in Islam.